2013
DOI: 10.1080/03650340.2013.789869
|View full text |Cite
|
Sign up to set email alerts
|

Soil enzyme activities in dependence on tree litter and season of a social forest, Burdwan, India

Abstract: The study was done to evaluate enzyme activities (amylase, cellulase and invertase) from the soils of different vegetation sites, with seasonal variation, of social forest, Burdwan, India. Study results showed significant lower enzymatic activities in the subsoil compared to those of the topsoil. The seasonal variations indicated that amylase, cellulase and invertase enzyme activities had reached peaks during the rainy seasons in different soil depths. Amylase activity was highest in Tectona litter containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
2
3
0
Order By: Relevance
“…In this study, enzyme activities (except for polyphenol oxidase) decreased with soil depth and the findings are similar to Lemanowicz and Krzyżaniak [54], Biró et al [55] and Das et al [56]. No consistent temporal trends were observed among soil enzyme activities, however, at the second crop growing stage, i.e., in July (summer in study area), most soil enzymes appeared higher activities, probably because soil enzyme activities increase with the rise of soil temperature [57].…”
Section: Discussionsupporting
confidence: 79%
“…In this study, enzyme activities (except for polyphenol oxidase) decreased with soil depth and the findings are similar to Lemanowicz and Krzyżaniak [54], Biró et al [55] and Das et al [56]. No consistent temporal trends were observed among soil enzyme activities, however, at the second crop growing stage, i.e., in July (summer in study area), most soil enzymes appeared higher activities, probably because soil enzyme activities increase with the rise of soil temperature [57].…”
Section: Discussionsupporting
confidence: 79%
“…The activities of the soil enzymes urease, amylase, and invertase did not vary significantly (p > 0.05) from season to season but the seasonal variation of cellulase activity was significant (p < 0.01). Similar higher level of cellulase activity during rainy season was reported by Das et al (2014). The seasonal variation results revealed that amylase activity in the As-contaminated area was significantly (p < 0.000) different from that of the control area during pre-monsoon period.…”
Section: Soil Enzyme Activitiessupporting
confidence: 87%
“…This is probably due to the different availability of nutrient is different in different soils (Olander & Vitousek 2000;Treseder & Vitousek 2001). Moreover, nitrogen potentially alter soil organic matter, therefore, it may have indirect effects on soil enzyme activities (Cusack 2013;Das et al 2014). The dendrogram study revealed that As formed cluster with cellulase activity, but the other three enzymes activities do not form such cluster with As.…”
Section: Archives Of Agronomy and Soil Science 81mentioning
confidence: 89%
See 1 more Smart Citation
“…T 4 treatments showed substantially lower vigor index in Dalbergia sissoo (0.075) than Albizia lebbeck (1.39). Das et al, (2012) reported that with the increasing the concentration of leachate of Shorea robusta, the vigour index of the Cicer aretinum decreased. The vigour index of all the four seedlings may be due to reduced seed germination and shoot length, as vigour index is the product of germination and seedling growth.…”
Section: Vigor Indexmentioning
confidence: 99%